"I'm not the best at art": An exploration of children's growing sense of artistry within an outdoor, arts-based intervention. (June 2022) - Hallam, Dr. Jenny; Gallagher, Mrs. Laurel; Owen, Dr. Kay
Highlights: The visual arts support wellbeing, personal development and thinking. English primary school children receive a limited art education. Community-based art intervention informed by a youth-led approach supported artistry. Collaboration between schools and community groups should be encouraged. Abstract: This paper uses a case study approach informed by ethnography to explore children's engagement with an outdoor, arts-based intervention run by Urban Wilderness. Over the course of three two-and-a-half-hour sessions, 10 children (aged between 9-10 years old) worked with two Urban Wilderness facilitators and a professional artist to create a piece of art which was exhibited at a locally based family arts festival. Each session was recorded using audio and video equipment. These recordings, along with photographs, field notes and interviews were collated and analysed using interpretive ethnography. Analysis centres on three themes – drawing inspiration from the outdoor environment, developing the design, and choosing the design. Within the analysis, particular consideration is given to the experiences and artistic journeys of two boys who participated in the intervention; specifically, their lack of artistic confidence, their attempts to adopt differing approaches, and the support mechanisms utilised by adult facilitators. It is argued that in a time when art is being increasingly squeezed out of the English National Curriculum, community run art interventions can play a valuable role in supporting artistry in children and developing their identity as artists.